Nidificación del Jilguero Austral (Sicalis lebruni) en Sierra de la Ventana, provincia de Buenos Aires, Argentina - Cozzani , Natalia C.; Zalba, Sergio M.; Mattos, Evangelina; Sarria, Rodolfo (Nuestras Aves, 2008)
Este artículo no cuenta con un resumen.